Effects of Aloe Vera/Chitosan Ratios on the Tensile Properties of Aloe Vera/Chitosan/Polyvinyl Alcohol Nanofibrous Membranes for Wound Care Dressing - Sosiati, Harini; Rahman, Abdul; Sahputra, Kelvin Kurniawan; Ibnul Fatoni, Miftahul Faruq (UI Scholars Hub, 2025)
Chitosan (CS) and Aloe vera (AV) are functional and antibacterial materials compatible with polyvinyl alcohol (PVA), which confers medical and healthcare potential. This study prepared and then characterized the influence of CS/AV ratios on the tensile properties of CS/AV/PVA nanofibrous membranes for wound care dressing materials. The CS/AV/PVA membranes were fabricated using an electrospinning technique at varying AV/CS/PVA volume ratios: 0:0:100, 0:20:80, 5:15:80, 10:10:80, 15:5:80, and 20:0:80. All membranes were subjected to tensile testing as per the ASTM 882 standard, and the nanofiber’s morphology was examined using scanning electron microscopy. Changes in the tensile strength related to the formation of the nanofiber morphology were evaluated to select the potential membranes for applications and then compared to those of commercial adhesive bandages. The addition of 20% CS to PVA (0:20:80) decreased the tensile properties. However, the addition of AV to CS/PVA increased the tensile strength and strain but decreased the tensile modulus. Further, the 15AV/5CS/80PVA and 20AV/PVA (20:0:80) nanofibrous membranes exhibited superior tensile properties than other membranes and commercial adhesive bandages. Based on its tensile properties and double antibacterial agent content, the nanofiber membrane of 15AV/5CS/80PVA is suggested as a potential membrane for wound care dressings.